Evaluasi Efektivitas Pengelolaan Sampah TPS 3R Melalui Pemilahan dari Sumber - Fara Nesya Ananditya; Dian Dinanti; Mustika Anggraeni (Pusat riset dan Inovasi Nasional, 2026)
Urban waste management has become a complex challenge due to population growth, urbanization, and economic activities contributing to higher waste generation. Effective waste management systems are required to reduce waste disposed at final disposal sites. This study aims to evaluate the effectiveness of waste management at the TPS 3R Pedalangan Bersinar facility in Semarang City by examining waste separation from the source. The research applied a quantitative approach using mass balance analysis to assess the balance between incoming waste, processed waste, and residual waste in the system. Primary data were collected through field observations, interviews, and operational monitoring for six consecutive days, while secondary data were obtained from the Semarang Environmental Agency. Results show community-based waste banks in Pedalangan demonstrate a high level of effectiveness with a recovery factor reaching 100%, indicating optimal recycling performance and strong community participation. Meanwhile, the TPS 3R facility processes an average waste volume of 16.61 m³/day with reduction of 10.32 m³/day and residual waste of 6.29 m³/day, resulting in a recovery factor of approximately 0.62 categorized as moderate effectiveness. Therefore, strengthening household waste separation, improving operational management, and increasing community participation are recommended to enhance waste reduction and support sustainable urban waste management systems.